ANALISIS PREFERENSI TERHADAP PEMBELIAN CHINESE FOOD MELALUI GO FOOD DI KECAMATAN RUNGKUT - Sanjaya, Yogi; Winarno, Sri Tjondro; Indah, Pawana Nur (Yayasan Education and Social Center, 2024)
This research aims to analyze consumer preferences for purchasing Chinese Food through Go Food in the Rungkut sub-district and determine consumer considerations when purchasing Chinese Food by using Importance and Performance (IPA) and Customer Satisfaction Index (CSI) data analysis methods. This research shows consumer preferences for attributes when purchasing Chinese Food through Go Food. Characteristics of the respondents of this study in purchasing Chinese Food through Food in the Rungkut sub-district: Most of the respondents were female, with an average age of 16-25 years, taking into account the attributes of consumer satisfaction level with the product, Ease of information, presentation and ordering security. Consumer satisfaction with purchasing Chinese Food through Go Food is 76.23%, included in the category 76% < CSI ≤ 100%, which means consumers feel very satisfied